Study Of Tremulous Signatures In Devanagari Nepali Script - Pradhan, Mukul; Bajracharya, Madhumati; Rai, Manisha; Shakya, Piyush Man; KC, Basudev; Bhusal, Bishnu Prasad (Scientific World, 2021)
Signatures, as one of the behavioral human characteristics are generally recognized as legal means for verifying an individual's identity by administrative and financial institutions. A signature is developed by a person and it can change over time. Signatures are prone to influences by age, physical and mental conditions. In this study tremulous signatures including questioned and standards related to 50 real cases resolved by National Forensic Science Laboratory of Nepal were collected. The time interval between questioned and standard signatures was up to ten years. Sixteen major characteristics along with their forty-one sub characteristics of each case were studied. Among sixteen major characteristics in the tremulous signatures, study shows that the characteristics like the style of writing in hand printed form, pen pauses, medium pen pressure, poor line quality, pen lifts are most prominently observed. Tremors were absent mostly in the terminal strokes of letters. The letters written were varied in size and those were 6% small, 70% medium and 24% large. Interestingly no any retouch attempts were found to complete the shape of letters.